Dynamics of SuperCalc4 - Yu, John W.; Harrison, David (Illinois : Dow Jones-Irwin, 1987)
This book is about SuperCalc4, a state-of-the-art spreadsheet program developed by Computer Associates International, Inc., As an integrated program with spreadsheet, data management, and graphics capabilities, it is ideally suited to any business or industry situation where information is in the form of numbers and their relationship.
Part 1. Basic techniques with SuperCalc4 -- Part 2. Advanced features -- Part 3. Sample business and personal applications.
Keywords: COMPUTER PROGRAMMING